Bibliometric and Collaborative Network Analysis on Active Methodologies in Education - Adrián Segura-Robles; María Elena Parra-González; Miguel Ángel Gallardo-Vigil (Springer, 2020)
Abstract Teachers have gradually been making more use of active methodologies at all educational levels, and some even carry out research in this area. The objective of this research was to develop a bibliometric study in order to gain an in-depth view of the scientific literature on active methodologies in education. An analysis of the classic descriptions of bibliometrics, co-authorship indexes and collaboration networks was carried out, using documents indexed by the Web of Science on active methodologies in education between 2009 and 2019. The final data corpus is composed of 513 documents. The results show that publications on this type of research are booming, demonstrating a growing interest in these kinds of studies in the short and medium term. English is the predominant language in these studies, as occurs in the general scientific literature. The results indicate a limited range of topics being studied currently and likely growth in coming years. Therefore, this category of research can be considered as a relevant field of study for the scientific community in the short and medium term.